2021
DOI: 10.1002/ijc.33501
|View full text |Cite
|
Sign up to set email alerts
|

Race, ethnicity and risk of second primary contralateral breast cancer in the United States

Abstract: Breast cancer survivors have a high risk of a second primary contralateral breast cancer (CBC), but there are few studies of CBC risk in racial/ethnic minority populations. We examined whether the incidence and risk factors for CBC differed by race/ethnicity in the United States. Women with a first invasive Stage I‐IIB breast cancer diagnosis at ages 20‐74 years between 2000 and 2015 in the Surveillance, Epidemiology, and End Results Program (SEER) 18 registries were followed through 2016 for a diagnosis of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
(83 reference statements)
2
12
0
Order By: Relevance
“…Future research should explore population representative datasets to study racial/ethnic differences in CPM use and associated predictors. A recent study of nearly 460,000 women showed that, compared to NH White women, NH Black and Hispanic women have an increased risk of contralateral breast cancer that is not explained by available clinical or socioeconomic factors that did not include germline mutation data [ 27 ]. Future studies should explore racial/ethnic differences in predisposition to contralateral breast cancer and the consequent need for CPM use.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should explore population representative datasets to study racial/ethnic differences in CPM use and associated predictors. A recent study of nearly 460,000 women showed that, compared to NH White women, NH Black and Hispanic women have an increased risk of contralateral breast cancer that is not explained by available clinical or socioeconomic factors that did not include germline mutation data [ 27 ]. Future studies should explore racial/ethnic differences in predisposition to contralateral breast cancer and the consequent need for CPM use.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-, 10-, and 15-year risks of CBC for each gene were estimated from cumulative incidence curves. A multivariate proportional hazard regression analysis accounting for competing risk of death 15 was performed to compare the CBC risk between PV carriers in each of the five genes and non-PV carriers when adjusting for study, age of diagnosis, 16-18 race/ethnicity, 19,20 menopausal status, 21 histology 22,23 and estrogen receptor (ER) status 24 of the first breast cancer, and use of endocrine therapy. Further analyses stratified by ER status, menopausal status, race/ethnicity, and age of diagnosis of first breast cancer were performed, adjusting for all relevant covariates in the original model.…”
Section: Methodsmentioning
confidence: 99%
“…The changes in average dose to the contralateral breast in the general population of all breast cancer patients remains unclear and will require dosimetric analysis of large populations recruited from diverse treatment centers and continued follow-up in the next decades. Such studies could also address changes in cardiac dose (45) as well as disparities in radiationassociated outcomes (8,46). There were no observed differences in dose received to the contralateral breast by tumor size, estrogen receptor status, receipt of chemotherapy or hormonal therapy, or patient age at time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…These second breast cancers account for 40% of all new malignancies for survivors of breast cancer (2)(3)(4). The risk of CBC is associated with characteristics of the patient and first breast tumor (5)(6)(7)(8), treatment received for the first breast cancer (9,10), and radiation dose received to the untreated contralateral breast during radiation therapy (9)(10)(11)(12)(13)(14). The dose received to the contralateral breast is associated with a proportional increase in risk of CBC, primarily for young women treated at ,40 years of age (14,15).…”
Section: Introductionmentioning
confidence: 99%